(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
This essay is an excerptum from the master’s degree thesis I notabilia manzoniani editi e inediti al Teatro comico fiorentino. It aims at introducing the main features of the edition with commentary of Manzoni’s notabilia to XVI century Tuscan playwrights’ works, focusing on Giovan Maria Cecchi’s five comedies, included in the first two volumes of Teatro comico fiorentino. These notabilia have therefore been copied in the extract they belong to; moreover they have been accurately explained and compared with Manzoni’s marginalia to Crusca Veronese and to Plauto’s comedies. Finally, we have studied how Manzoni reused these notabilia in the different drafts of The Betrothed (maxime in the so-called Seconda minuta). This analysis helps examine in depth the linguistic contribution given to the novel by Cecchi, whose works are rich in Florentine puns and idioms. It also paves the way for a new linguistic commentary of the novel, especially of the 1825-1827 edition, whose «tosco-milanese» language is wildly comparable to Manzoni’s bookish perusals before the well-known «wash on the banks of the Arno».